(untitled) (Journal of Educational Sciences, 2021)
The promotion of Kazakhstani higher education institutions (HEI) in world university rankings is one of the priorities of the public policy in the field of higher education. The corresponding target indicators are reflected both in the President’s adresses to the people of Kazakhstan and in the state programs for the development of education and science. This strategy of the state is aimed at improving the quality of educational services in higher education and transforming Kazakhstani HEI into research universities, which in the future should become hubs for an innovative, knowledge-based economy. This article analyzes the indicators for assessing universities in the world rankings QS, THE, positions and scores of Kazakhstani universities. The strategic documents of several universities of Kazakhstan, as well as internal mechanisms aimed at achieving target indicators for advancement in world rankings, are considered. It was found that Kazakhstani universities are gaining higher scores on indicators related to academic and reputation activities. The level of funding, attracting young talents and leading scientists, including foreign ones, publication activity in the world’s leading journals are the main factors in promoting the university in world rankings, directly and indirectly influencing its position. Key words: world university rankings, Kazakhstani HEI, target indicators, internal rating systems.